Advances in library administration and organization. Vol. 20 - Williams, Delmus Eugene; Garten, Edward D. (Emerald, 2003)
Volume 20 includes important contributions to the field from the UK, Germany, and the United States. These deal with the evolving role of the chief information officer, information ethics, library services at a distance, e-metrics, and continuous quality improvement.
Includes index.
Keywords: Language Arts & Disciplines -- Library & Information Science -- General.; Medical -- General.; Library, archive & information management.; Library administration.; elektronické knihy; electronic books